The Impact of Corporate Social Responsibility, Audit Committee, and Financial Performance on Firm Value - Zulfa Rosharlianti; Aziza Pratiwi (Jurnal Akuntansi Trisakti, 2022)
This study aims to determine the impact of Corporate Social Responsibility, audit committee and financial performance on firm value. The population in this study is the consumer goods industrial sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period as many as 64 companies. The example of this examination was dictated by purposive testing technique and got 31 organizations recorded on the Indonesia Stock Exchange (IDX) for the 2017-2019 period so the all out example was 93 perceptions. The type of data used is secondary data obtained online through the www.idx.com. Speculation testing in this investigation utilizing various straight relapse examination. The test tool used is Eviews 9. The results of this study indicate that simultaneously Corporate Social Responsibility, audit committee and financial performance have a positive and significant effect on firm value. Partially, Corporate Social Responsibility has a negative and insignificant effect on firm value, while the audit committee and financial performance have a negative and significant effect on firm value.